Antara Tanggung Jawab dan Karir (Gambaran Adversity Quotient pada Guru Pembimbing Khusus) - Irmanuelan Mangansige; Doddy Hendro Wibowo (Universitas Kristen Maranatha, 2020)
The purpose of this study was to determine the description of the adversity quotient of special/resource teacher with honorary status, in facing the challenge of difficult situations during their duties and responsibilities in the career. The research method used is qualitative with a case study approach. The data collection method used interviews with interview guidelines based on the adversity quotient theory. Participants in this study were two special/resource teachers with honorary statuses in Salatiga city. The results of the study explained that both participants were aware of and could face difficult situations that came from other people and from within themselves. Besides, the character and social support shown can influence both participants in their actions and help them to survive difficult situations. Keywords: adversity quotient, special/resource teacher, honorary teacher.